Longitudinal Changes in Resting State Connectivity and White Matter Integrity in Adolescents With Sports-Related Concussion. (24th August 2018) - Murdaugh, Donna L.; King, Tricia Z.; Sun, Binjian; Jones, Richard A.; Ono, Kim E.; Reisner, Andrew; Burns, Thomas G.
Abstract: Objectives: The aim of this study was to investigate alterations in functional connectivity, white matter integrity, and cognitive abilities due to sports-related concussion (SRC) in adolescents using a prospective longitudinal design.Methods: We assessed male high school football players (ages 14–18) with ( n =16) and without ( n =12) SRC using complementary resting state functional MRI (rs-fMRI) and diffusion tensor imaging (DTI) along with cognitive performance using the Immediate Post-Concussive Assessment and Cognitive Testing (ImPACT). We assessed both changes at the acute phase (<7 days post-SRC) and at 21 days later, as well as, differences between athletes with SRC and age- and team-matched control athletes.Results: The results revealed rs-fMRI hyperconnectivity within posterior brain regions (e.g., precuneus and cerebellum), and hypoconnectivity in more anterior areas (e.g., inferior and middle frontal gyri) when comparing SRC group to control group acutely. Performance on the ImPACT (visual/verbal memory composites) was correlated with resting state network connectivity at both time points. DTI results revealed altered diffusion in the SRC group along a segment of the corticospinal tract and the superior longitudinal fasciculus in the acute phase of SRC. No differences between the SRC group and control group were seen at follow-up imaging.Conclusions: Acute effects of SRC are associated with both hyperconnectivity and hypoconnectivity, with disruption of white matter integrity. In addition, acute memory performance was most sensitive to these changes. After 21 days, adolescents with SRC returned to baseline performance, although chronic hyperconnectivity of these regions could place these adolescents at greater risk for secondary neuropathological changes, necessitating future follow-up. ( JINS, 2018, 24, 781–792)